Link Model Simulations of International Trade: An Evaluation of the Effects of Currency Realignment - Johnson, Keith; Klein, Lawrence R. (Journal of Finance, 1974)
Keith Johnson, Lawrence R. Klein, Link Model Simulations of International Trade: An Evaluation of the Effects of Currency Realignment, The Journal of Finance, Vol. 29, No. 2, Papers and Proceedings of the Thirty-Second Annual Meeting of the American Finance Association, New York, New York, December 28-30, 1973 (May, 1974), pp. 617-630